HEAVING TYPE WAVE ENERGY CONVERTER ANALYSIS WITH CASE STUDY AT WEH ISLAND-ACEH OFFSHORE AREA - Agni, Ismail
Indonesia is a country where 70% of its territory filled by ocean and has quite large wave energy potential of 10 – 20 kW/m. However, the wave energy potential cannot be utilized yet to support the energy needs of both households and industries in Indonesia. This is due to the unavailability of a Wave Energy Converter (WEC) device that has a profitable economic value. On the other hand, this becomes an opportunity for researchers to develop WEC that can reach operational and economic goals. This research discusses one type of WEC, namely the Heaving Buoy which has a relatively simple way of working and its feasible to be combined with other energy converter systems such as Solar Panels to increase its economic value. In general, this thesis discusses three studies, namely a study of variations in hydrodynamic parameters, a study of geometric variations, and a buoy configuration optimization for case studies at Weh Island-Aceh offshore area. An analysis on each dimension and shape is carried out related to performance and hydrodynamic parameters to become the basis for determining the optimum dimensions and geometry. The results of the analysis based on wave with 2m high and 3 – 18 seconds period show that a buoy with 5m diameter, hemisphere submerged surface shape, and 7500 kg/s PTO Damping is the optimum buoy configuration and shape. Furthermore, an application study was carried out in the offshore area of Pulau Weh using selected buoy shape by adjusting the buoy configuration so that it could work optimally at that particular location. According to the analysis results, it can be concluded that a buoy with a hemispherical submerged surface shape, 7m diameter, 15m draft, and 200,000 kg/s PTO Damping is the most optimum configuration for operation on Weh Island-Aceh area with 245.98 MWh AEP and 18.79%. efficiency.